Morbidity in primary care Epidemiologic data from Family Medicine Network - Luijks, Hilde; Van de Laar, Floris Alexander; Schers, Henk (Radboud University Press, 2023)
Morbidity in primary care' is a medical textbook that presents a selection of diseases, disorders and clusters of symptoms registered in 'Family Medicine Network' (FaMe-Net). FaMe-Net is a Dutch primary care registration network with decades of experience in the accurate registration of all morbidity presented to the GP. This registration is embedded in the daily practice of GPs providing regular care to their enrolled patients. All morbidity data from 2014 up to and including 2021 can be accessed at www.famenet.nl/morbidity-data. Each chapter presents the incidence and prevalence of the selected condition and the age and sex groups in which this condition is most common. Common reasons for encounter are described: symptoms, complaints or requests that patients present to their GP at the beginning of the episode of care. In addition, each chapter discusses common GP interventions (policy). The clinical course and registration of the condition are also described. Reading the chapters in this book familiarises the user with how epidemiological numbers can be found on the website. The chapters contain links to the web pages where the relevant data are displayed. This makes it an interactive textbook, as the user can apply their own selections and look up their own epidemiological question. For example, change the calendar period or answer the same question for a different condition, including conditions not yet described in this book. The accompanying text in the chapters helps interpret the numbers correctly and guard against potential pitfalls. This book is thus dynamically linked to the website. The topics have been carefully selected and present epidemiological data of both brief episodic and chronic conditions, harmless and more serious conditions, and also include so-called symptom diagnoses that occur regularly in primary care, such as 'sleep disorders'. The database and this book are updated periodically. The FaMe-Net registration network is unique in systematically recording the patient's reason for encounter in every contact with the GP (practice), and the interventions carried out, such as radiology/imaging, laboratory diagnostics, prescription of medication and referrals to primary and secondary care. This allows the correlation between reason for encounter, final diagnosis and interventions to be visualised. This book is written by general practitioners practising in registering practices, many of whom are also affiliated with Radboud University Medical Centre as researchers, lecturers or trainers. The book is intended for general practitioners, GPs in training, medical students and researchers.